DIGITAL COMPETENCES AND INNOVATIONS IN HUMAN RESOURCES DEVELOPMENT IN UKRAINE IN MODERN REALITIES - Спіцина, А.; Любарець, В.В.; Горідько, Н.; Голова, І.Г.; Нестеренко, О.О. (SWorldJournal, 2025)
The use of innovative human resource management strategies in the context of digital transformation has become not only a necessary requirement for enterprise development but also a key determinant of competitiveness in the current global market environme